Reconocimiento del patrimonio, caso de estudio la Peña, Cundinamarca (2022)
The subject of study is focused on the deterioration of cultural heritage and its characteristics, present in small municipalities, category 6, and its rural peripheries, where there is evidence of loss of identity and cultural roots, in the same way the little investment destined for conservation. of the cultural heritage of each region.